The importance of trap type, trap colour and capture liquid for catching Dendrolimus pini and their impact on by‐catch of beneficial insects. (27th June 2020) - Sukovata, Lidia; Dziuk, Aleksander; Parratt, Matthew; Bystrowski, Cezary; Dainton, Katrina; Polaszek, Andrew; Moore, Roger
Abstract: Dendrolimus pini can be a serious defoliator of pine trees in some European countries. The monitoring of this insect is important, but no single standardized capture technique exists for monitoring purposes. A range of insect trap types (delta sticky, G‐trap, Unitrap and cross‐vane Unitrap), colours (green, red and white delta traps and yellow and green cross‐vane Unitraps) and types of capture liquid (glycol and salt solutions) were tested to determine the most effective trap for D. pini monitoring. Trap colour (yellow and green) was also tested for beneficial Hymenoptera and Diptera. The Unitraps and cross‐vane Unitraps were the most effective trap types, but the latter trap that contained glycol solution was less effective than a dry trap. Trap colour did not have any effect on the catches of D. pini, but yellow Unitraps captured more Diptera (Phoridae and Tachinidae) and Hymenoptera (Pteromalidae, Ceraphronidae and Braconidae) than green traps. In contrast, the egg parasitoid Telenomus tetratomus preferred green traps. Overall catches of beneficial insects were relatively low, except Phoridae. The Unitraps are recommended for the efficient monitoring of D. pini unless other factors such as trap cost or remote monitoring locations justify the use of other traps.